Donor-Matched Comparison of Chondrogenic Potential of Equine Bone Marrow- and Synovial Fluid-Derived Mesenchymal Stem Cells: Implications for Cartilage Tissue Regeneration - Zayed, Mohammed; Caniglia, Christopher; Misk, Nabil; Dhar, Madhu S. (Frontiers in Veterinary Science, 2017)
Mesenchymal stem cells (MSCs) have been demonstrated to be useful for cartilage tissue regeneration. Bone marrow (BM) and synovial fluid (SF) are promising sources for MSCs to be used in cartilage regeneration. In order to improve the clinical outcomes, it is recommended that prior to clinical use, the cellular properties and specifically, their chondrogenic potential must be investigated. The purpose of this study is to compare and better understand the in vitro chondrogenic potential of equine BMMSCs and SFMSCs populated from the same equine donor. Bone marrow and SF derived MSCs cultures were generated from five equine donors, and the MSCs were evaluated in vitro for their morphology, proliferation, tri-lineage differentiation and immunophenotyping. Differences in their chondrogenic potentials were further evaluated quantitatively using glycosaminoglycan (GAG) content and via immunofluorescence (IF) of chondrogenic differentiation protein markers, SOX9, Aggrecan and Collagen II. The BMMSCs and SFMSCs were similar in cellular morphology, viability and immunophenotype, but, varied in their chondrogenic potential, and expression of the key chondrogenic proteins. The SFMSCs exhibited a significant increase in GAG content compared to the BMMSCs (P <0.0001) in 3 donors, suggesting increased levels of chondrogenesis. The expression of the key chondrogenic proteins correlated positively with the GAG content, suggesting that the differentiation process is dependent on the expression of the target proteins in these 3 donors. Our findings suggest that even though SFMSCs were hypothesized to be more chondrogenic relative to BMMSCs, there was considerable donor-to-donor variation in the primary cultures of MSCs which can significantly affect their downstream application.